Artificial Intelligence and its Impact on Management Research: A Large-Scale Bibliometric Topic Mapping Analysis of the Interval 2020-2023 - Cristian VIDU (Revista de Management Comparat International)
The field of artificial intelligence is starting to permeate all aspects of society and management is no exception. From digital transformation, marketing and industry 4.0 to privacy and ethics, the significant growth of the number of papers being published each year makes it difficult to assess the state of research, the current topics that academia is focusing on and how these topics are evolving over the years. This paper aims to highlight the main topics of this complex and central theme and showcase the evolution of the field through a structured bibliometric analysis of all business-relevant articles and conference paper published in this interval. Leveraging the SCOPUS database, a number of 4763 papers have been identified and analysed, revealing a number of new insights into how the study of artificial intelligence is evolving. Although we are looking at a global perspective, in subsidiary we also observe and compare how Romania is faring against the other global players.